2019
DOI: 10.1007/s10826-019-01605-3
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Descriptions of How Their Psychosis Affects Parenting

Abstract: Objectives Parental psychosis poses a risk factor for a child's well-being. Few studies have focused on the parents' views of how their psychosis affects their parenting, and results for parenting ability in this group are contradictory. The present study aimed to explore how parents with psychosis experience the effect(s) of their illness on parenting. Methods In-depth and semi-structured interviews were conducted with 15 parents who attended outpatient clinics specializing in psychosis. The transcripts were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 40 publications
3
25
0
Order By: Relevance
“…It is possible that supporting parents in this area requires more directed support; for example, by professionals actually initiating and taking part in school meetings, in case, it would be perceived as beneficial for the child. Furthermore, for children to participate in leisure activities, the fact that previous studies show that many parents with psychosis encounter poverty (Campbell et al, 2012; Park, Solomon & Mandell, 2006; Strand, Boström, & Grip, 2020) may be a concrete hindrance to promoting resilience, and cannot be sufficiently met by an intervention focusing mainly on communication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that supporting parents in this area requires more directed support; for example, by professionals actually initiating and taking part in school meetings, in case, it would be perceived as beneficial for the child. Furthermore, for children to participate in leisure activities, the fact that previous studies show that many parents with psychosis encounter poverty (Campbell et al, 2012; Park, Solomon & Mandell, 2006; Strand, Boström, & Grip, 2020) may be a concrete hindrance to promoting resilience, and cannot be sufficiently met by an intervention focusing mainly on communication.…”
Section: Discussionmentioning
confidence: 99%
“…One study found that 50% of fathers and 36% of mothers were identified with severe impairments in parenting (Campbell et al, 2012). Another study reported that parents with psychosis described impairments in all parenting domains (Strand, Boström, & Grip, 2020), and specifically mentioned that depression, fatigue, and difficulty focusing because of hearing voices had a negative impact on their ability to provide protection, reciprocity, and control. Many parents with psychosis also encounter unemployment, poverty, isolation, and stigmatization (Campbell et al, 2012; Park, Solomon & Mandell, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This is much so when the parents have serious mental illness. For example, parents with psychosis have reported that depression, hearing voices and fatigue impacted their abilities to provide protection, reciprocity and control for their children (Strand et al, 2020). Mothers, especially, attach pride to their parenting role.…”
Section: Adding Salt To Wounds?mentioning
confidence: 99%
“…Parental mental illness can impair parenting capacity to the extent that children are burdened with responsibilities for protecting and caring for their parents and siblings (Simpson-Adkins & Daiches, 2018; Van Parys et al, 2015). An outcome of parental mental illness is the parent’s experience of difficulties in performing their parental or caregiving responsibilities at optimum levels (Strand et al, 2020). In cases where the parent with mental illness fails to perform their caregiving role, role reversal between the parent and the child may take place where the child begins to take care of other members in the family including the parent (Van Parys et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The complex task of parenting is more challenging for parents with severe mental illness (Campbell et al, 2012; Wan & Green, 2009). Parents with psychosis describe that depression, fatigue, and difficulty focusing negatively impact their ability to provide protection, reciprocity, control, and routines (Strand et al, 2020). Mothers with psychosis struggle with maintaining discipline, boundaries, and their parental role while experiencing symptoms or side effects of medication, and worry about the possible effects of their illness on their children (Dolman et al, 2013).…”
Section: Introductionmentioning
confidence: 99%